Geochemistry, provenance, and tectonic significance of sedimentary rocks of the Middle to Late Devonian McArras Brook and Visean Martin Road formations, Merigomish Subbasin, northern Antigonish Highlands, Nova Scotia - Murphy, J. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2001)
The Merigomish Subbasin occurs along the southern Hank of the composite Laic Devonian Permian Maritimes Basin of Atlantic Canada. The subbasin consists predominantly of Visean to Westphalian clastic rocks that overlie Middle to Late Devonian basalt and continental clastic rocks of the McArras Brook Formation. The McArras Brook Formation is uneonformably overlain by a 120 meter thick Late Visean clastic sequence of the Manm Road Formation, which represents the oldest rocks deposited in the Merigomish Subbasin. Cieochemical and isoiopic attributes of representative samples of the clastic rocks in the McArras Brook and Martin Road Ibrmaiions were investigated in order to constrain their respective provenance and to investigate the regional tectonic significance of the angular unconformity that separates them. The clastic rocks selected for analysis have clast sizes ranging from 1 to 4 mm in diameter. The geochemistry and isotopic signatures of the clastic rocks in these formations arc so similar that they arc interpreted to have been derived from the same source region. Both formations are characterized by a limited range in Si(): (65 78 wt. %), wider ranges in other major elements such as MgO and Fe20,, relatively constant TVNb. moderate LREE enrichment (La'Smn - 3 6 1.1), relatively flat HRFF. patterns (Tb/Yb„ = 1.3-1.4) strongly negative (ȷ values (-6 5 to -7.7. calculated for a 320 Ma depositional age), and high Tdm values (ranging from ca.1.5 to 16 Ga) Taken together, the geochemical and isotopic signature of the McArras Brook and Martin Road formations suggest that they were predominantly derived from local Silurian siliciclaslic rocks of the Arisaig Group in the Antigonish Highlands Ihc isotopic data also suggest an important contribution from the Mcguma tcrranc to the south The data are compatible with local sources, and ihe geochemical similarity between ihc McArras Brwk and Martin Road formations suggests that ihc angular unconformity that separates them is of local, rather than regional, significance.